Mutational signatures of ionizing radiation in second malignancies - Sam Behjati (Nature Portfolio, 2016)
Ionizing radiation may induce irreparable DNA damage leading to cancer. Here, the authors identify a specific signature of mutations arising in patients exposed to ionizing radiation and suggest that radiation-induced tumorigenesis is associated with higher rates of genome-wide deletions and balanced inversions.